Digital Twin Technology in Archaeology: Laser Scanning Ancient Metallurgical Galleries at Agios Sostis, Sifnos - Vassilakis, Emm.; Gavalas, G.; Konsolaki, A.; Kazantzaki, M; Tsakalos, E (4th International Symposium on Geotechnical Engineering for the Preservation of Monuments and Historic Sites)
This study presents the comprehensive three-dimensional documentation of two ancient metallurgical galleries at Agios Sostis, on the island of Sifnos, Western Cyclades (Greece). Sifnos has long been a significant center of mining activity, with evidence dating back to the late 4th millennium BC. Its basement rocks are rich in mineral deposits, including argentiferous lead, copper, iron, and zinc resources that played a catalytic role from prehistoric times. The exploitation of these metalliferous deposits, one of the key stages in the transition from the Stone Age to the Bronze Age, contributed significantly to the islands cultural development.Data acquisition was performed using high-resolution terrestrial laser scanning from multiple fixed positions within each gallery, complemented by handheld laser scanning to capture narrow and irregular sections. Topographic control was ensured through the establishment of numerous Ground Control Points (GCPs), enabling high spatial accuracy. The surface topography above the galleries and the adjacent slag mounds was documented using photogrammetric processing of imagery collected via Unmanned Aerial Systems (UAS), producing orthoimages with ground sampling distances of 4.18 cm and 1.62 cm.The interior laser scanning datasets, comprising over 500 million georeferenced 3D points, were processed into dense point clouds and further transformed into high-resolution digital terrain models and textured meshes using specialized software and a structured methodology. By integrating subsurface and surface data, overburden thicknesses ranging from 5.2 m to 66.8 m were calculated, and the volumetric estimation of metallurgical slag deposits was determined to be approximately 4,914 m³.This Digital Twin approach underscores the potential of advanced geospatial techniques for the documentation and protection of vulnerable archaeological heritage. It offers a transferable and scalable framework for similar fragile environments.